Atividade microbiológica em solos de vinhedos com histórico de adubação nitrogenada - Palermo, Natália Moreira (2024)
Fertilization in vineyards is carried out when the soils do not meet the nutrient needs of the vines. However, with the increase in demands for sustainable viticultural practices in the face of climate change and new consumption patterns, it is essential to understand how continuous fertilization can alter soil properties, affecting its physical, chemical, and biological quality. Urease enzyme (RH) activity and microbial biomass are important indicators of soil health and sensitive to management practices. However, there are few studies evaluating the impact of prolonged cultivation of grapevines and nitrogen mineral fertilization on the activity of urease and soil microbial biomass, and the relationship of these parameters with fruit production and quality. This research aims to evaluate the variation in the enzymatic activity and microbial biomass of soils (BMS) of vineyards, with a history of nitrogen fertilization, at different times and places of soil collection, and to relate these variations with nutritional and productive variables and the composition of the must. An experiment was conducted over 12 years with different annual doses of nitrogen fertilizer (0, 40 and 80 kg N ha-1 year-1 ) to evaluate how these practices influence RH and BMS activity. Sampling was carried out at different phenological stages (full flowering, berry color change and postharvest) of the vines and in two distinct areas: the grapevine line and the inter-rows. The nutrient contents in the soil and plant tissue of the grapevines were determined. The activity of UR and BMS were analyzed and correlated with the production and quality of grapes. The results showed that RH activity was significantly affected by the interaction between nitrogen doses and collection times. In general, urease activity was higher at lower doses of N, especially at full flowering. In contrast, BMS did not show a direct relationship with N doses, remaining stable or even increasing in areas with higher N application. In the grapevine row, urease activity was consistently higher than in the interrows, indicating the influence of grapevines on higher RH exudation. The activity of RH and BMS varied with the phenological stage of the grapevines and the climatic variables, highlighting the complexity of the interactions between fertilization, soil health and grape composition.